2012
DOI: 10.15365/joce.1502092013
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining the Heart: Attracting Latino Families to Inner-City Catholic Schools

Abstract: , is faced with many challenges: filling empty seats; supporting increased costs; and, possible closure. The small parish is primarily Latino, but few parish families are enrolled in the school. This action research project used in-depth interviews to examine parishioner-parent perspectives on the importance of Catholic education in the Latino community. Understanding the perspectives of parishioner-parents is a key step toward the ultimate goal of developing a marketing plan that attracts and engages Latino f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Some studies investigated curricular, community-based, or organizational interventions and programs designed to enhance the experiences of stakeholder groups in current Catholic schools (Beltramo, 2012;Gibbs et al, 2009;Madden, 2017;Palomino-Bach & Fisher, 2017;Proehl et al, 2013;Rieckhoff, 2014;Scanlan, 2017;Suhy, 2012). As established in previous sections, urban Catholic educators are very aware their schools have not consistently provided stakeholders supportive or educative environments, particularly the low-income communities and communities of color these schools consider themselves mission-bound to serve.…”
Section: Categories Of Reform Efforts Designed To Sustain the Legacy Of Urban Catholic Schoolingmentioning
confidence: 99%
“…Some studies investigated curricular, community-based, or organizational interventions and programs designed to enhance the experiences of stakeholder groups in current Catholic schools (Beltramo, 2012;Gibbs et al, 2009;Madden, 2017;Palomino-Bach & Fisher, 2017;Proehl et al, 2013;Rieckhoff, 2014;Scanlan, 2017;Suhy, 2012). As established in previous sections, urban Catholic educators are very aware their schools have not consistently provided stakeholders supportive or educative environments, particularly the low-income communities and communities of color these schools consider themselves mission-bound to serve.…”
Section: Categories Of Reform Efforts Designed To Sustain the Legacy Of Urban Catholic Schoolingmentioning
confidence: 99%
“…Catholic parents who attended church regularly were more likely to send their children to Catholic school (Sander, 2005). In the Latino community, Suhy (2012) found that urban parents had a strong preference for Catholic education for their children. Furthermore, Sander (2001) stated that people who had attended a Catholic school were more likely to regularly attend Mass, pray daily, and retain their Catholic identity as adults.…”
Section: Religion Values and Beliefsmentioning
confidence: 99%
“…And for the first time, the number of 18-to 24-year-old Latino youth enrolled in college exceeded two million, reaching a record 16.5% of all college enrollments (Fry & Lopez, 2012). As students in nursery school progress through kindergarten and into elementary school and high school, Latino students are expected to become an even larger share of all school enrollments, including Catholic schools-where today only 15% of the students are identified as Latino (NCEA, 2015) and only 3% of all Latino students enrolled in elementary and secondary education attend Catholic schools (Suhy, 2012). 7 In the last decade, the graduation rates for Latino students across the country have improved.…”
Section: Latino Enrollment and Graduation Ratesmentioning
confidence: 99%